Pendampingan dalam Memahami Indeks Kebahagiaan Guru di Madrasah Aliyah Negeri (MAN) di Tangerang Selatan - Nurochim Nurochim; Siti Ngaisah (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2020)
The educational environment is a place where a group of people gather for a long time. In addition, the school is an educational institution that aims to achieve the vision and mission of education. Principals and teachers are human resources, as the driving force for achieving educational goals. Therefore these human resources must be managed properly. Good management starts with understanding the individual, that is feeling happy. Feelings of happiness will make the education human resources can carry out their duties properly. Therefore, community empowerment is important to be implemented to understand the meaning of happiness. The result of this empowerment is that the teacher's happy feelings are quite high. This is seen from the understanding of each dimension namely life satisfaction, feelings, and the meaning of life. However, there are sub-dimensions that are still low, such as conditions for career advancement and teacher competence, and the lack of teacher opportunities to improve academic quality. It is therefore important for policy makers to carry out further studies and empowerment based on teachers. So the teacher can carry out the task well. Keyword: teacher, happiness, life satiscaftion, affect, meaning of life Abstrak Lingkungan pendidikan merupakan tempat sekelompok orang berkumpul dalam waktu yang lama. Selain itu sekolah merupakan salah satu lembaga pendidikan yang bertujuan untuk mencapai visi dan misi pendidikan. Kepala sekolah dan guru merupakan sumber daya manusia, sebagai penggerak tercapainya tujuan pendidikan. Oleh karena itu sumber daya manusia tersebut harus dikelola dengan baik. Pengelolaan yang baik dimulai dengan memahami individu, yakni perasaan bahagia. Perasaan bahagia akan membuat sumber daya manusia pendidikan dapat melaksanakan tugasnya dengan baik. Oleh kerena itu pemberdayaan masyarakat penting dilaksanakan untuk memahami makna kebahagiaan tersebut. Hasil pemberdayaan ini adalah menunjukkan perasaan bahagia guru cukup tinggi. Hal tersebut dilihat dari pemahaman masing-masing dimensi yakni kepuasan hidup, perasaan, dan makna hidup. Namun demikian, ada sub dimensi yang masih rendah, seperti kondisi peningkatan karir dan kompetensi guru, dan kurangnya kesempatan guru untuk meningkatkan kualitas akademik. Oleh karena itu penting bagi para pemangku kebijakan untuk melaksanakan kajian dan pemberdayaan lebih lanjut yang berbasis pada guru. Sehingga guru dapat melaksanakan tugas dengan baik. Kata Kunci: guru; kebahagiaan; kepuasan hidup; perasaan; makna hidup